Literature Review: Integration Of Molecular Docking, ADMET Prediction, And Chemical Modification Of Indonesian Natural Compounds As Anticancer Candidates - Saeful Amin; Riski Fauzi; Gita Syifa Salsabilla; Silka Gina Fitriyani (International Journal of Health Engineering and Technology, 2026)
As one of the highest drivers of mortality at the global level, cancer is identified through unregulated cell proliferation. This condition urges researchers to immediately find new therapeutic agents that have a superior safety and efficacy profile. This review analyzes the (CADD) approach, especially the integration of molecular docking, ADMET prediction, and chemical modification, as an important strategy in exploring Indonesian natural product compounds as anticancer candidates. This research aims to review the integrative role of these three approaches in increasing the potential of natural compounds as lead compounds. The method used is a systematic literature review from the Google Scholar and PubMed databases. The results of a review of various studies show that the in silico approach via molecular docking has succeeded in identifying potential compounds such as squalene, berberine, and quercetin with high binding affinity to cancer targets such as NUDT5, HER2, and EGFR. ADMET prediction and drug-likeness testing (Lipinski's Rule) confirm the pharmacokinetic and safety profiles of drug candidates. Furthermore, chemical modifications to lead compounds such as curcumin and gallic acid were proven to increase significantly stability and cytotoxic activity. The integration of this method makes an important contribution in accelerating the discovery of new drugs, reducing research costs, and increasing the opportunities.